The thermal diffusivity of molecular cryocrystals - Sumarokov, V.V.; Jeżowski, A.; Stachowiak, P.; Freiman, Y.A. (Физика низких температур, 2019)
Low-temperature thermal diffusivity of molecular cryocrystals (O₂, N₂, CO, N₂O and CO₂) has been investigated and some anomalies were found. The thermal diffusivity of these crystals vary by more than 4–6 orders of the magnitude in the temperature range from 1 K up to their triple points. The thermal diffusivity displays jumps at the phase transition points. It has been found that the thermal diffusivity of solid oxygen is nonmonotonic. Below 4 K, the temperature dependence shows a plateau which is due to the fact that both the heat capacity and the thermal conductivity have the cubic temperature dependence in this temperature range. For the cryocrystals of the nitrogen group, a similar plateau is shifted to lower temperatures. The temperature dependence of the equalization time for these crystals is studied.